PENGARUH RASIO KEUANGAN, KEBIJAKAN DIVIDEN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN FOOD & BEVERAGE DI BURSA EFEK INDONESIA TAHUN 2021-2024 - Nadia Yaumi Lestari; Artie Arditha Rachman; Dian Nirmala Dewi (LPPM STIE Muhammadiah Bandung, 2026)
The Current study aims to analyze the effect of financial ratios, dividend policy, and company growth on firm value in the Food & Beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The financial ratios examined include liquidity measured by the Current Ratio, profitability measured by the Gross Profit Margin, and solvency measured by the Debt to Equity Ratio. Dividend policy is measured using the Dividend Payout Ratio, company growth is measured by Asset Growth, and firm value is measured using Price to Book Value (PBV). This study employs a quantitative approach using secondary data consisting of 168 research data points, which are analyzed using multiple linear regression. The results indicate that simultaneously (F-test), liquidity, profitability, solvency, dividend policy, and company growth have a significant effect on firm value. Partially (t-test), profitability, solvency, and company growth have a positive effect on firm value, while liquidity and dividend policy have no effect on firm value.